REBUILDING OF RAT INTESTINAL MUCOUS EPITHELIUM IN PRENATAL ONTOGENESIS - Vagnerova, Radomira; Kucera, Tomas (Biomedical papers, 2004)
Morphological differentiation of the intestinal epithelium in the laboratory rat occurs between the 16th and 21st day of prenatal development. The pseudostratified epithelium is rebuilt into simple epithelium of the future lining. A characteristic sign of this rebuilding is formation of primitive folds, villi and intraepithelial vacuoles coresponding in submicroscopic picture with a secondary luminization. On the tips of folds and villi groups of cells released from the epithelium are observed. In these cells expression of activated caspase-3 confirms the presence of apoptosis in the process of cell death during epithelium rebuilding.
Keywords: Rat intestinal epithelium/Prenatal differentiation/Apoptosis